Effect of Fiber Source and Crude Protein Level on Nursery Pig Performance - K. L. Batson; H. I. Calderón; M. D. Tokach; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2020)
A total of 360 pigs (200 × 400; DNA, Columbus, NE; initially = 11.0 lb) were used in a 45-d growth trial to evaluate the effects of fiber source and crude protein level on growth performance and fecal dry matter of nursery pigs. Upon arrival to the nursery research facility, pigs were randomly assigned to pens with 5 pigs per pen and 9 replicate pens per treatment. Dietary treatments were arranged in a 2 × 4 completely randomized factorial with main effects of crude protein (21 or 18% CP) and fiber source (none, coarse wheat bran, oat hulls, or cellulose; Arbocel, J. Rettenmaier USA, Schoolcraft, MI). Treatment diets were formulated in two dietary phases from d 0 to 10 and 10 to 24, with a common post-treatment diet fed from d 24 to 45. The 21% CP diets contained 1.40% standardized ileal digestible lysine (SID) in phase 1 and 1.35% SID Lys in phase 2. Treatment diets were formulated to a maximum SID Lys:digestible CP level of 6.35%, thus SID Lys decreased in the 18% CP (1.25% SID Lys) diets to maintain the ratio. Diets containing a fiber source were formulated to the level of insoluble fiber provided by 4% coarse wheat bran, resulting in the addition of 1.85% oat hulls and 1.55% cellulose to the respective diets. No fiber source × CP level interactions (P>0.05) were observed throughout the study. During the experimental period, decreasing dietary CP (and subsequently SID Lys) decreased (P= 0.05) ADG, and d 24 body weight (BW) and worsened feed efficiency (F/G). Average daily gain and d 45 BW decreased (P<0.05) for pigs fed 18% CP diets compared to pigs fed 21% CP diets overall from 0 to 45. Fecal dry matter on d 17 was increased (P<0.001) for pigs fed 18% CP diets compared to pigs fed 21% CP diets. No main effects of fiber source were observed for growth performance throughout the study. However, fecal dry matter percentage increased (P<0.05) for pigs fed added cellulose compared to pigs fed no fiber or coarse wheat bran on d 10 and 24 of the trial. Similarly, pigs fed cellulose had increased (P= 0.028) fecal dry matter compared to pigs fed no fiber, with pigs fed coarse wheat bran and oat hulls intermediate. In conclusion, reducing dietary crude protein resulted in decreased growth performance while minimal improvements in fecal dry matter were observed during the experimental period. The source or inclusion of insoluble fiber in nursery diets had no impact on performance. The inclusion of cellulose improved fecal dry matter compared to feeding no dietary fiber or coarse wheat bran.
Keywords: crude protein; fecal dry matter; insoluble fiber; nursery pig